2007
DOI: 10.1097/fbp.0b013e3282df3cde
|View full text |Cite
|
Sign up to set email alerts
|

The role of hippocampus in the pathophysiology of bipolar disorder

Abstract: Bipolar disorder (BD) is thought to be associated with abnormalities within discrete brain regions associated with emotional regulation, particularly in fronto-limbic-subcortical circuits. Several reviews have addressed the involvement of the prefrontal cortex in the pathophysiology of BD, whereas little attention has been given to the role of the hippocampus. This study critically reviews data from brain imaging, postmortem, neuropsychological, and preclinical studies, which suggested hippocampal abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 135 publications
5
100
1
3
Order By: Relevance
“…TLR2, but not TLR4, has also been implicated in the perpetuation of inflammatory responses in the CNS after pro-inflammatory stimulation of astrocytes [70] and involved in hippocampal neurogenesis as mice lacking TLR2 displayed impaired hippocampal and neuronal differentiation, which was not observed for TLR4 [71]. These observations could be related to the TLR2 specificity of our findings especially as hippocampal alterations have been repeatedly reported in adults with a history of childhood traumatic experiences and are suggested to be involved in the pathophysiology of BD [72][73][74].…”
Section: Discussionsupporting
confidence: 38%
“…TLR2, but not TLR4, has also been implicated in the perpetuation of inflammatory responses in the CNS after pro-inflammatory stimulation of astrocytes [70] and involved in hippocampal neurogenesis as mice lacking TLR2 displayed impaired hippocampal and neuronal differentiation, which was not observed for TLR4 [71]. These observations could be related to the TLR2 specificity of our findings especially as hippocampal alterations have been repeatedly reported in adults with a history of childhood traumatic experiences and are suggested to be involved in the pathophysiology of BD [72][73][74].…”
Section: Discussionsupporting
confidence: 38%
“…A postmortem study demonstrated reduced pyramidal cell size in the hippocampus of BD patients compared with healthy control subjects (Liu et al, 2007). Most previous in vivo studies also showed no difference in hippocampal volumes between BD patients and healthy subjects (Frey et al, 2007a), although a few studies have shown smaller hippocampal volumes in BD patients (Bearden et al, 2007;Frazier et al, 2005). Lithium and valproate, primary mood stabilizers for the pharmacological treatment of BD patients, increase BDNF concentration in the rat hippocampus .…”
Section: Discussionmentioning
confidence: 99%
“…Como verificado no presente trabalho, houve melhora em funções cognitivas associadas a circuitos neurocognitivos variados, incluindo o córtex pré-frontal, o hipocampo e o circuito límbico-fronto-estriatal. Alguns estudos já haviam relacionado essas áreas ao humor deprimido (Frey et al, 2007;Porter et al, 2007).…”
Section: Considerações Finaisunclassified